Using umgidi wokulingisa (dramatic stamping ritual) within drama therapy to provide an accessible therapeutic space for cultural beings with an African worldview - Seleme, Bandile (My University, 2017)
This mixed case study used a traditional umgidi (stamping ritual) as a dramatic re-enactment within drama therapy to provide a therapeutic space for fostering wellbeing of cultural beings with an African worldview (CBsAW). Culture is considered as a critical resource because it guides individuals in how to achieve wellbeing by using resources from their context. The praxis of umgidi wokulingisa was used in sessions as per guidelines offered through interviews with izinyanga (traditional healers). One session was conducted with two participants in Moutse East. The data was analysed using Interpretative Phenomenological Anyalysis (IPA) to discern emerging themes. Two superordinate themes emerged: experiences of a contextual self; and creative and flexible self-regulation. Experiences of a contextual self represents the participants’ cultural context and value system. Creative and flexible self-regulation is the developmental process of musicking in the therapeutic space that allows a participant to be self-conscious. By experiencing umgidi wokulingisa, the two participants appeared to shift their perspective on the accessibility of drama therapy within their cultures. The study was not able to explore the act of ukugiya due to a reluctance of community members to participate in the study. As a result of reluctance to participate in the study, I recommend a community intervention to ascertain how umgidi wokulingisa within drama therapy can manage expectations and concerns of the community within their cultural context and value system.
A research report submitted to the Faculty of Humanities University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts (Drama Therapy), 2017
Keywords: Drama--Therapeutic use--Africa; Dance therapy--Africa; Cultural psychiatry--Africa; Psychiatry, Transcultural--Africa